2018
DOI: 10.3324/haematol.2017.186320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characteristics of MEF2D fusion-positive B-cell precursor acute lymphoblastic leukemia in childhood, including a novel translocation resulting in MEF2D-HNRNPH1 gene fusion

Abstract: Fusion genes involving have recently been identified in precursor B-cell acute lymphoblastic leukemia, mutually exclusive of the common risk stratifying genetic abnormalities, although their true incidence and associated clinical characteristics remains unknown. We identified 16 acute lymphoblastic leukemia cases and 1 lymphoma case harboring fusions, including (n=10), (n=6) and one novel fusion. The incidence of fusions overall was 2.4% among consecutive B-cell acute lymphoblastic leukemia patients enrolled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 43 publications
5
75
0
Order By: Relevance
“…We conducted a randomized controlled trial comparing the efficacy of low-dose continuous cytarabine infusion with conventional cytarabine block in the consolidation phase in the SR/HR groups because of the excellent outcome reported for continuous cytarabine infusion in the OCLSG-94 trial 7 ; however, there was no significant difference in pEFS or pOS between the two arms. Recent studies have revealed that subtypes of B-ALL associated with poor prognosis, such as Ph-like ALL [16][17][18] , IKZF1plus ALL 19 , and MEF2D-rearranged ALL 20,21 , comprise a substantial proportion of B-ALL in the NCI-HR category. Consistent with these findings, we previously reported poor prognosis for patients with B-ALL with IKZF1 deletion in the JACLS ALL-02 study, particularly in NCI-HR or PPR patients 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a randomized controlled trial comparing the efficacy of low-dose continuous cytarabine infusion with conventional cytarabine block in the consolidation phase in the SR/HR groups because of the excellent outcome reported for continuous cytarabine infusion in the OCLSG-94 trial 7 ; however, there was no significant difference in pEFS or pOS between the two arms. Recent studies have revealed that subtypes of B-ALL associated with poor prognosis, such as Ph-like ALL [16][17][18] , IKZF1plus ALL 19 , and MEF2D-rearranged ALL 20,21 , comprise a substantial proportion of B-ALL in the NCI-HR category. Consistent with these findings, we previously reported poor prognosis for patients with B-ALL with IKZF1 deletion in the JACLS ALL-02 study, particularly in NCI-HR or PPR patients 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the karyotypes in our cell lines were highly biased in comparison with those in childhood BCP-ALL patients: 14 cell lines were BCR/ABL1-positive, 13 cell lines were TCF3/PBX1positive, 12 cell lines were MLL (KMT2A)-rearranged, and 3 cell lines were TCF3/HLF-positive. Furthermore, we later discovered that 15 cell lines were positive for MEF2D-fusions [18], which are recently identi ed fusion genes with a poor therapeutic outcome [19,20]. In contrast, only four cell lines were ETV6/RUNX1-positive, and no cell lines were hyperdiploid.…”
Section: Discussionmentioning
confidence: 99%
“…STIL-TAL1 cannot be classified into any family. 4.5 Along with the MEF2D-FM, ZNF384-FM, and PAX5-FM, which were recently reported in the literature, 14,[31][32][33][34][35] most of the FGs in hematological malignancies discovered to date can be clustered into about 20 major FG-FMs (Table 1). Furthermore, the content of FGs that can be covered in these FG-FMs far exceeds the known FGs in de facto.…”
Section: Classification and Recognition Of Fgs As "Fusion Gene Family"mentioning
confidence: 91%
“…21,32 FGs involving MEF2D have recently been identified in B-ALL, and the incidence of MEF2D-FGs overall was 2.4% in consecutive B-ALL patients in a single clinical trial. 33,34 MEF2D-FGs-positive patients frequently presented a cytoplasmic µ chain-positive, pre-B immunophenotype and often expressed an aberrant CD5 antigen. Elevated GATA3 expression was also a characteristic feature of MEF2D-FGs-positive patients, and PHF6 mutations showed an unexpectedly high frequency (50%) in them.…”
Section: Technological Advances and New Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation